Pengaruh Jenis Produk Cetakan, Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Percetakan CV Citra Jalan Sisingamangaraja No 33 Medan Amplas - Mukti, Ridho; Rahmat, Muhammad; Safina, WA Dian; Lubis, Tukimin (Movere Journal, 2024)
This study aims to reveal the effect of product type, price, and service quality on purchasing decisions at CV Citra printing. As objectives include to determine the effect of product type on purchasing decisions, to determine the effect of price on purchasing decisions, and to determine the effect of service quality on purchasing decisions. This study uses a descriptive quantitative approach with questionnaire data collection methods, interviews, and documentation. The population in this study are consumers of CV Citra and the sample as respondents of this study will be taken using probability sampling with the lemeshow formula, namely 80 consumers who were met during the research. The results of this study indicate that the calculated F value of 303.761 is greater than the F table of 2.49, which means that simultaneously there is an influence on the type of product (X1), price (X2), and service quality (X3) on purchasing decisions at CV Citra printing. Partially, it can be seen that only the variables of product type (X1) and price (X2) have an effect on purchasing decisions, namely the variable type of product (X1) of 3.546 is greater than the t table of 1.665 and service quality (X3) of 6.702 is greater than the t table of 1.665, while for the price variable (X2) of -1.163 is smaller than the t table of 1.665 which indicates that the price variable (X2) has no effect on purchasing decisions. Based on the results seen from the coefficient of determination, the variable product type (X1), price (X2), and service quality (X3) have an effect, namely with an R2 value of 0.923 or 92.3%. Keywords: Type of Product, Price, Services Quality, Purchasing Decisions